Perceived influence of oral health upon quality of life in heart transplant patients - Segura-Saint-Gerons, Rafael (Medicina Oral S.L., 2012)
Objective: A study was made of heart transplant patient perception of the influence of oral health upon quality of life, based on the Oral Health Impact Profile (OHIP-49) questionnaire validated for Spanish speaking subjects. Design: A cross-sectional evaluation was made of the heart transplant patients followed-up on in the Heart Transplantation Unit of Reina Sofía University Hospital (Spain), using the OHIP-49 questionnaire. The included patients were all over age 18 and signed the corresponding informed consent to participation in the study. The data were entered in a database and analyzed using the SPSS statistical package. Results: A total of 150 heart transplant patients (118 males and 32 females, with a mean age of 54.94 years; range 19-79) were studied. The subjects showed a poor perceived influence of oral health upon quality of life, with a mean score of 24.43 out of a possible total of 196 points. Women showed significantly improved perception of the influence of oral health upon quality of life versus men. Conclusions: The subjects in our study showed a poor perceived influence of oral health upon quality of life.